The impact of various grape stock cultivars on the As, Cu, Co and Zn content of the grape berry (must, seed) - Fekete, István; Rakonczás, Nándor; Andrási, Dávid; Bódi, Éva; Szilágyi, Szilárd; Kovács, Béla (Acta Agraria Debreceniensis, 2013)
Scientific research from the last decades showed that the inappropriate industrial and agricultural production caused an abnormal increase of the potentially toxic elements in the soil. Unfortunately the acidification of the soil is an increasing problem in Hungary. According to Várallyay et al. (2008) 13% of the Hungarian soils are highly acid. Accumulation of toxic elements differs in the genetically diverse plant species. The root of the plant constitutes a filter so that the rootstock is also kind of a filter system, which may prevent that the scion part (such as berry) accumulate high levels of various potentially toxic elements from the soil. The aim of research was to determine how different grape rootstocks influence the As, Co, Cu and Zn content of the musts and seeds. Thus, specifying which of the grape rootstocks takes up the lowest level of these 4 elements (As, Co, Cu and Zn), and accumulates in berries, so could reduce the potentially toxic element load of the grape berries. The grape rootstock collection of the University of Debrecen was set up in 2003 in 3x1 m spacing on immune sandy soil. Grafting of ‘Cserszegi fűszeres’ was started in 2010. We could evaluate yields harvested from 12 rootstock varieties of the experiment in October 2011. We obtained valuable differences in the arsenic, copper, cobalt and zinc concentrations of musts and seeds of ‘Cserszegi fűszeres’ grafted into different rootstocks. The results obtained from the 2011 harvest support the statement that the choice of rootstock might be an important factor to increase food safety. The differences in concentration of the four elements observed in case of the rootstock may have been caused on one hand by the rootstock effect, and on the other hand, the vintage effect has a very significant impact on the vines element uptake. Several years of experimental results will be needed to answer these questions.